"Full-plastic jacket" with everolimus-eluting Absorb bioresorbable vascular scaffolds: Clinical outcomes in the multicenter prospective RAI registry (ClinicalTrials.gov Identifier: NCT02298413). (1st September 2018) - Tarantini, Giuseppe; Masiero, Giulia; Fovino, Luca Nai; Mojoli, Marco; Varricchio, Attilio; Loi, Bruno; Gistri, Roberto; Misuraca, Leonardo; Gabrielli, Gabriele; Cortese, Bernardo; Pisano, Francesco; Moretti, Luciano; et al.
Abstract: Objectives: The objective of this study was to investigate mid-term clinical outcomes of patients treated with 'full-plastic jacket' (FPJ) everolimus-eluting Absorb bioresorbable vascular scaffold (BRS) implantation. Background: FPJ with BRS may represent an interesting option for patient with diffuse coronary artery disease (CAD), but data on the clinical impact of FPJ using the Absorb BRS are scant. Methods: FPJ was defined as the implantation of >56 mm of overlapping BRS in at least one vessel. We compared outcomes of patients receiving Absorb FPJ vs. non-FPJ within the multicenter prospective RAI Registry. Results: Out of 1505 consecutive patients enrolled in the RAI registry, 1384 were eligible for this analysis. Of these, 143 (10.3%) were treated with BRS FPJ. At a median follow-up of 649 days, no differences were observed between FPJ and non-FPJ groups in terms of the device-oriented composite endpoint (DoCE) (5.6% vs. 4.4%, p = 0.675) or the patient-related composite endpoint (PoCE) (20.9% vs. 15.9%, p = 0.149). Patients receiving FPJ had higher rates of target vessel repeat revascularization (TVR) (11.2% vs. 6.3%, p = 0.042). In the FPJ group, there was no cardiac death and only one (very late) stent thrombosis (ST) (0.7%). Conclusions: Mid-term outcomes of a FPJ PCI strategy in the setting of diffuse CAD did not show a significant increase in composite device- and patient-related events, with rates of cardiac death and ST comparable to non-FPJ Absorb BRS implantation. However, these findings are hypothesis generating and requiring further validation. Highlights: FPJ treatment might be feasible in a population with a high clinical and angiographic risk profile. A high adherence to the BRS specific implantation protocol remains crucial. The treatment of CTO by FPJ might be a predictor of adverse outcome.